Development and evaluation of novel alginate/cockle shell powder nano-biocomposite porous 3D scaffold for bone repair - Bharatham, B. Hemabarathy (2013)
Shells are comparable to bones of vertebrates due to the similarities in mechanical properties and strength. The cockle shell material may act as an anolog of calcium carbonate in an in vivo condition that makes it a potential bone grafting material. The present study involves the development and evaluation of a novel three-dimensional alginate/nano cockle shell powder biocomposite bone scaffold prepared through lyophilization and divalent cation cross-linking methods. Element analysis revealed that the shell material consisted of 96% of calcium carbonate with no traces of toxic elements while physiochemical analysis revealed a predominantly aragonite form of calcium carbonate polymorph. The cockle shell powder was converted to nano particles using a biomineralization catalyst through a simple chemical method and was used as a representative of the inorganic phase while sodium alginic acid (alginate) was used as the organic phase in the development of the nano-biocomposite scaffold. The scaffold mixture was prepared in varying composition ratios, characterized and evaluated through various characterization studies. Scanning electron microscopy (SEM) analysis revealed the micro architecture of the scaffolds with pore size ranging from 10 – 336 μm diameters. The porosity of the scaffolds was found to be above 60%. Mechanical properties of the tested scaffolds showed the composition ratio of 40% alginate and 60% nano cockle powder (Alg:nCP=40:60) possesed favorable mechanical properties ranging between the spongy bone structures compressive strength. Swelling ratio of the scaffolds showed an average of 30% medium uptake ability with 20 – 30% changes in diameter. Enzymatic degradation test revealed an increase in structural stability proportional to the amount of nano cockle shell powder within the composition while pH changes observed during degradation studies revealed a neutralizing effect of nano cockle shell powder towards the potential acidification of the solution during alginate degradation. The physiochemical properties of the materials and the subsequent chemical interactions evaluated revealed the phase purity of the materials as well as the scaffolds ionic interaction characteristics contributing to an increase in thermal stability. In-vitro studies conducted on MG63 human osteoblast-like cells revealed good biocompatibility and absences of cytotoxic effect of the scaffolds with higher cell viability noted in scaffolds of 40:60 ratio and was used for further in-vitro evaluation. Cell growth and adherence towards the scaffold materials were evaluated for a period of 48 hours, 7 and 14 days using SEM, Element Detection System (EDS) and histological evaluation. The results showed good attachment and spreading properties of the cells within 48 hours and were found to have grown into large cell clusters by Day 7 with distinctive presence of calcium nodules that was verified using EDS analysis on the nano-biocomposite scaffolds. At Day 14, a completely mineralized scaffold structure was observed in the nano-biocomposite scaffolds supported by findings from EDS analysis that showed the presence of phosphate and calcium as well as histological observations showing presence of osteoid like tissues.In-vivo analysis of the scaffold implanted in a 5 mm osseous defect at the proximal part of the left tibia bone of New Zealand White rabbits revealed evidence of better healing quality of the nano-biocomposite scaffolds compared to control scaffolds as well as empty unfilled defects that were created simultaneously on the right proximal tibia bone of the animals. The quality of healing assessed after seven weeks post implantation through histomorphometric evaluations at three different depths of the defects revealed a significantly better healing in the nano-biocomposite defect site at all three sections compared to the empty defect site as well as with the lower section of the control scaffold defect site. Comparatively, the regeneration of bone tissues were found to occur in a systematic coordinated way with larger areas of matured bone tissues observed in the presences of the nano-biocomposite scaffolds. The remaining void spaces within the defect sites with implants were found to be significantly lesser compared to those of the empty defects while the amount of remaining nano-bicomposite scaffold material was found to be significantly higher compared to the control scaffolds at all three regions evaluated. Statistical analysis for all data’s were done using One-way Analysis of Variance (ANOVA) followed by the post-hoc Tukey’s test, unless otherwise stated, where p<0.05 was accepted as significant. As a conclusion, the developed nano-biocomposite scaffold using alginate and nano cockle shell powder was found to show promising results to be used in the field of bone tissue engineering. The scaffolds showed good porous architectures that enhance its osteoconductive properties by facilitating better and faster bone regeneration in addition to being completely biocompatible as well as a cost effective alternative for bone grafting in the near future.